ABOUT INTUITION MECHANISMS IN THE CONTEXT OF HUMAN ACTIVITY - Oleg Maltsev ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The human activity is the object of the conducted research, the mechanisms of intuition is its subject. Therefore, the purpose of this article is statements of a philosophical comprehension of intuition mechanisms functioning in human activity. The main ideas of the author experienced the corresponding approbation in scientific and field researches of 2015-2020. They are systemically stated and presented in this article for the first time, as well. The innovation of the following article consists of the conducted research issues that reflect the systematization of knowledge of the mechanisms of intuition which result in a philosophical comprehension of the principles of operation of human memory blocks. Researches of a dialectic contradiction rational and irrational, activity development sources hold concrete manifestations of a contradiction in an intuition and goal setting connection, uniting of consciousness and memory. For this reason there comes a requirement to consider the main mechanisms of memory, namely: the prototipology memory block, archetypology memory block, and the ancestral unconscious block which integrity is defined by the memory model.